Associações de historiadores no Brasil: a SBPH entre lugares, normas e grupos (1961-2005) - Silva, Bruna (2019)
The path taken by this work concerns the formation of groups of historians in Brazil, especially the Sociedade Brasileira de Pesquisa Histórica – SBPH, which emerged from the Associação de Professores Universitários de História. The research investigated the historical context of SBPH’s emergence and functioning. To this end, an extensive universe of historical sources was used: interviews, official documents, the Revista Brasileira de História, annals, books, letters, among other sources, which allowed us to question the social place of historical research in Brazil, between 1961 and 2005. The time frame took into consideration the year of foundation of the APUH, today ANPUH, passing through the creation of the SBPH, until the publication of the periodical publications and the other activities of this society.